GLYCOLATE OXIDASE3, a Glycolate Oxidase Homolog of Yeast l-Lactate Cytochrome c Oxidoreductase, Supports l-Lactate Oxidation in Roots of Arabidopsis. Issue 2 (5th August 2015) - Engqvist, Martin K.M.; Schmitz, Jessica; Gertzmann, Anke; Florian, Alexandra; Jaspert, Nils; Arif, Muhammad; Balazadeh, Salma; Mueller-Roeber, Bernd; Fernie, Alisdair R.; Maurino, Veronica G.
Abstract : A glycolate oxidase metabolizes l -lactate to pyruvate in vivo and may ensure the maintenance of low levels of l -lactate after its formation under normoxia. Abstract: In roots of Arabidopsis ( Arabidopsis thaliana ), l -lactate is generated by the reduction of pyruvate via l -lactate dehydrogenase, but this enzyme does not efficiently catalyze the reverse reaction. Here, we identify the Arabidopsis glycolate oxidase (GOX) paralogs GOX1, GOX2, and GOX3 as putative l -lactate-metabolizing enzymes based on their homology to CYB2, the l -lactate cytochrome c oxidoreductase from the yeast Saccharomyces cerevisiae . We found that GOX3 uses l -lactate with a similar efficiency to glycolate; in contrast, the photorespiratory isoforms GOX1 and GOX2, which share similar enzymatic properties, use glycolate with much higher efficiencies than l -lactate. The key factor making GOX3 more efficient with l -lactate than GOX1 and GOX2 is a 5- to 10-fold lower K  m for the substrate. Consequently, only GOX3 can efficiently metabolize l -lactate at low intracellular concentrations. Isotope tracer experiments as well as substrate toxicity tests using GOX3 loss-of-function and overexpressor plants indicate that l -lactate is metabolized in vivo by GOX3. Moreover, GOX3 rescues the lethal growth phenotype of a yeast strain lacking CYB2, which cannot grow on l -lactate as a sole carbon source. GOX3 is predominantly present in roots and mature to aging leaves but is largely absent from young photosynthetic leaves, indicating that it plays a role predominantly in heterotrophic rather than autotrophic tissues, at least under standard growth conditions. In roots of plants grown under normoxic conditions, loss of function of GOX3 induces metabolic rearrangements that mirror wild-type responses under hypoxia. Thus, we identified GOX3 as the enzyme that metabolizes l -lactate to pyruvate in vivo and hypothesize that it may ensure the sustainment of low levels of l -lactate after its formation under normoxia.